DEVELOPMENT OF SCIENCE LEARNING VIDEO-BASED LOCAL POTENTIAL RIVER TUBING TO IMPROVE CRITICAL THINKING SKILLS STUDENTS OF TEMPUREJO 2 STATE JUNIOR HIGH SCHOOL - Ana Wardatul Jannah; Mahla Noer Rozqiyah Syam; Mifathul Hasanah; Tanti Lutfiatul Hidayah; Sri Wahyuni (Program Studi Pendidikan IPA FKIP Universitas Jember, 2022)
River Tubing's local potential-based learning video is an alternative for developing learning tools by implementing local potential into science learning. This research is a development research that uses the Plomp development model which is adjusted to 4 stages. This study aims to describe the validity of River Tubing's local potential-based science learning videos, find out the practicality of River Tubing's local potential-based science learning videos in terms of the implementation of learning using science learning videos, and determine the effectiveness of River Tubing's science learning videos. Tubing's local potential-based science learning video in terms of ability. students' critical thinking and to find out student responses. River Tubing's local potential-based science learning video on substance pressure material in junior high school is valid with a final validity result of 60%-80% in the fairly valid category. Field trials were conducted in class VIII B of SMP Negeri 2 Tempurejo with 32 students. The results of practicality show that the level of implementation reaches a fairly practical category, namely 70% p <80% and the results of the effectiveness of using student critical thinking skills tests and student response questionnaires, student responses to science learning videos based on local potential River Tubing can be said to be good if the student response category is minimal pretty good category.